On the Form and Interpretation of Echo Wh-Questions. (28th June 2018) - Beck, Sigrid; Reis, Marga
Abstract: We argue that echo wh -questions (E wh Qs) are autonomous grammatical structures, and that their distinctive formal properties determine their semantics and pragmatics. Echo wh -sentences contain a wh -phrase in which the wh -element is narrowly focused, and a phrasal Q operator. Wh -phrase and Q operator determine a question semantics. Focus on wh determines the discourse appropriateness conditions for E wh Qs, namely that an answer to the question be given in the context. A compositional analysis is provided that derives this interpretation.